2000
DOI: 10.1074/jbc.m004366200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Peroxisomal Pex5p from Rat Liver

Abstract: Pex5p is the receptor for the vast majority of peroxisomal matrix proteins. Here, we show that about 15% of rat liver Pex5p is found in the peroxisomal fraction representing 0.06% of total peroxisomal protein. This population of Pex5p displays all the characteristics of an intrinsic membrane protein. Protease protection assays indicate that this pool of Pex5p has domains exposed on both sides of the peroxisomal membrane. The strong interaction of Pex5p with the membrane of the organelle is not affected by mild… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 109 publications
(48 citation statements)
references
References 41 publications
3
45
0
Order By: Relevance
“…A cDNA encoding the 373 amino acids of human Pex3p (39) was amplified from human skin fibroblast total RNA by reverse transcription-PCR exactly as described before (38) using the primers 5Ј-CGCGTCGACATGCTGAGGTCTG-TATG-3Ј and 5Ј-CGCGTCGACTCATTTCTCCAGTTGCT-3Ј. The 1.1-kilobase pair cDNA fragment was cloned into the pGEM-T Easy vector according to the manufacturer's instructions (Promega).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cDNA encoding the 373 amino acids of human Pex3p (39) was amplified from human skin fibroblast total RNA by reverse transcription-PCR exactly as described before (38) using the primers 5Ј-CGCGTCGACATGCTGAGGTCTG-TATG-3Ј and 5Ј-CGCGTCGACTCATTTCTCCAGTTGCT-3Ј. The 1.1-kilobase pair cDNA fragment was cloned into the pGEM-T Easy vector according to the manufacturer's instructions (Promega).…”
Section: Methodsmentioning
confidence: 99%
“…In antibody inhibition experiments, purified IgGs (8 g) in SEM buffer were added to PNS fractions in import buffer and incubated for 20 min on ice before starting the import reaction with the 35 S-labeled reporter protein. Proteinase K treatment (400 g/ml final concentration) of import reactions in the absence or presence of detergents (1% (w/v) Triton X-100, 0.5% (w/v) sodium deoxycholate), sedimentation of organelles by centrifugation, treatment of organelle pellets with Na 2 CO 3 , pH 11.5 (37), or with solutions of high and low ionic strengths, protein precipitation with trichloroacetic acid, and SDS-PAGE analysis were done exactly as described before (38). Routinely, the gels were blotted onto a nitrocellulose membrane, exposed to an x-ray film, and afterward probed with several antibodies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It consists of incubating 35 S-labeled Pex5p with a post-nuclear supernatant from rat liver, and it explores the fact that Pex5p acquires a protease-resistant status when inserted into the peroxisomal membrane (38,39). By using this experimental strategy, it was shown that insertion of Pex5p into the peroxisomal membrane requires the presence of PTS1-containing proteins in the import medium and depends on available Pex14p, an intrinsic membrane component of the peroxisomal docking/translocation machinery (39,40).…”
mentioning
confidence: 99%
“…overrepresentation of Pex14 in the membrane complex involving Pex5 (Gouveia et al, 2000). Interestingly, not only the Cterminal part of Pex5 that encodes the cargo-binding domain reaches into the peroxisomal matrix (Gouveia et al, 2003a), but also the N-terminal sequence (Dammai and Subramani, 2001).…”
Section: Subramanimentioning
confidence: 99%